(untitled) (Indonesian Economic Justice Review, 2025)
This paper investigates the persistent economic inequality between urban and rural populations in Indonesia, a nation characterized by rapid urbanization yet significant rural poverty. While Indonesia’s cities have experienced substantial economic growth, rural areas, especially those in the outer provinces, have not seen similar levels of prosperity, resulting in stark disparities in income, education, and access to services. The study critically examines existing government policies aimed at addressing this divide, such as rural infrastructure development, agricultural subsidies, and rural entrepreneurship programs. It evaluates the effectiveness of these policies in promoting economic inclusion and bridging the urban-rural gap. Through a review of rural development programs, the paper assesses whether such policies have empowered rural communities or merely provided temporary relief without addressing structural issues like land ownership, access to education, and healthcare. The paper also explores the role of rural-to-urban migration in perpetuating inequalities and the social impacts of economic exclusion in rural areas. Finally, the study proposes a set of policy recommendations to promote more inclusive growth, such as investing in education, improving rural healthcare, enhancing agricultural productivity, and ensuring equitable access to urban economic opportunities.